The Effect Of Organizational Culture And Organizational Communication On Employees Performance - Bahrul Yaman; Neneng Hardiyanti; Lili Supriyadi (Enrichment : Journal of Management, 2022)
This research aims to find and produce an analysis of the influence of organizational culture and organizational communication on employee performance of PT Pos Indonesia (Persero) Bogor. Respondents in this research were employees who work in the PT Pos Indonesia environment, especially in Bogor. The number of respondents sampled in this research were 67 people and based on the purposive sampling method. This research uses multiple linear regression analysis techniques or models. Based on the above method, the results of this research indicate that organizational culture and organizational communication have a significant partially and simultaneously effect on the employee performance of PT Pos Indonesia Bogor and the percentage shows that as much as 57% of employee performance can be explained by organizational culture and organizational communication.